Choroideremia: molecular mechanisms and development of AAV gene therapy - Patrício, M; Barnard, A; Xue, K; MacLaren, R (Taylor and Francis, 2018)
Introduction: Choroideremia is an X-linked inherited retinal degeneration that causes blindness in afflicted males by middle age. The causative gene, CHM, plays a key role in intracellular trafficking pathways, and its disruption impairs cell homeostasis. Areas covered: The mechanism by which mutations in CHM cause choroideremia is still under debate. Here we describe the molecular defects in choroideremia cells regarding both the deficiency of prenylation and the involvement of Rab GTPases. Important in vivo and in vitro studies that contributed to the current knowledge are also discussed. Finally, the rationale for the development of a treatment strategy using AAV for gene replacement is presented, together with other treatment strategies under consideration. Expert opinion: Despite ubiquitous expression of the CHM gene, the primary defect in choroideremia is driven by retinal pigment epithelium (RPE) and photoreceptors degeneration. Here we discuss how impairment of vesicular trafficking pathways in the RPE plays a major role in the molecular pathogenesis of choroideremia. Moreover, this defect is likely restored by subretinal delivery of a functional copy of CHM using AAV, as evidenced by clinical trial results. The surgical complexity of delivering the AAV vector to the target area remains as the main challenge to this therapy. Abbreviations: AAV: adeno-associated virus; BCD: Bietti’s crystalline dystrophy; CHM: choroideremia; CHML: choroideremia-like; Dfp: days post-fertilization; EMA: European Medicines Agency; ERG: electroretinogram; ETDRS: Early Treatment Diabetic Retinopathy Study; FDA: Food and Drug Administration; FTase: farnesyl transferase; GFP: green fluorescent protein; GGPP: geranylgeranyl-diphosphate; GGTase-I: geranylgeranyl transferase type-I; GGTase-II: geranylgeranyl transferase type-II; HMG-CoA: 3-hydroxy-3-methylglutayl-CoA; HMGCR: HMG-CoA reductase; iPSC: induced pluripotent stem cells; IRDs: inherited retinal diseases; KO: knockout; LCA: Leber congenital amaurosis; NMD: nonsense-mediated mRNA decay; OCT: optical coherence tomography; PMBCs: peripheral blood mononuclear cells; POS: photoreceptor outer segments; PTCs: premature termination codons; Rab GGTase: Rab geranylgeranyl transferase; REP: Rab escort protein; RPE: retinal pigment epithelium; TRIDs: translational read-through inducing drugs; WPRE: woodchuck post-transcriptional regulatory element.